TÓPICA E INDUÇÃO: os limites do raciocínio indutivo pautados em formalismos lógicos no âmbito da técnica do pensamento problemático proposta por Theodor Viehweg - Assis, Sidney Geraldo Cota de (2021)
This research treats about the limits of inductive reasoning based on logical formalisms in the Legal Topic proposed by Theodor Viehweg. The main objectives concern in a) the demonstration of the defective character of induction as a process of inference qualified by the probability or verisimilitude judgment of its conclusions in where is the nature of the Aristotelian dialectic discourse contrary to the apodictic modus; b) the confirmation that the Legal Topic conceived as a technique of problematic thinking in Theodor Viehweg is essentially inductive so it presents a flawed aspect. The methodology used for this is the bibliographic review/research whose authors and listed theories are discussed from the logical implicative method of the textual dissertative-argumentative kind. This way, it is concluded that the topic being substantially inductive is linked to the defective character of this reasoning without being unfeasible and completely alienate from Law, but only in a few areas.